2008
DOI: 10.1021/ja805850q
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transport and Recombination in Solid-State Dye Solar Cell with Spiro-OMeTAD as Hole Conductor

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
382
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 428 publications
(407 citation statements)
references
References 29 publications
17
382
1
5
Order By: Relevance
“…It is not possible to determine in a straightforward manner the part of the IS spectra that contains information about chemical capacitance, see Supplementary Note 1 for further discussions. The IS spectra have been fitted using equivalent circuits previously used for solid DSSC utilizing spiro-MeOTAD 22 . The use of spiro-MeOTAD as the HTM adds an extra degree of complexity to the analysis, as has been pointed out recently 23 , and in some cases it introduces an additional R-C feature to the TL circuit.…”
Section: Performancementioning
confidence: 99%
See 2 more Smart Citations
“…It is not possible to determine in a straightforward manner the part of the IS spectra that contains information about chemical capacitance, see Supplementary Note 1 for further discussions. The IS spectra have been fitted using equivalent circuits previously used for solid DSSC utilizing spiro-MeOTAD 22 . The use of spiro-MeOTAD as the HTM adds an extra degree of complexity to the analysis, as has been pointed out recently 23 , and in some cases it introduces an additional R-C feature to the TL circuit.…”
Section: Performancementioning
confidence: 99%
“…Nyquist plots for two different applied DC signals, V app , are shown in the graphs. Solid lines are the fits obtained using equivalent circuits previously used for solid DSSC with spiro-MeOTAD, 22 and in some cases additional R-C feature to the TL for an accurate fitting, see Supplementary Fig. S9.…”
Section: Performancementioning
confidence: 99%
See 1 more Smart Citation
“…14 It is well known from the previous experience in Dye Sensitized Solar Cells (DSCs) that the solar cell performance is increased significantly when additives as 4-tert-butylpyridine and lithium bis(trifluoromethylsulphonyl)imide are added to the spiro-OMeTAD layer. 18 In addition, it has also been reported that certain complexes, such as tris[2-(1H-pyrazol-1-yl)-4-tertbutylpyridine)] cobalt(III) tris(bis(trifluoromethylsulfonyl)imide) (Co(PyPyz) 3 In this paper we report the development of a new Ir complex, IrCp*Cl(PyPyz) [TFSI], Fig. 1(a), which has been used as additive to spiro-OMeTAD in PSCs, with the aim of improving the properties of the HTM layer and consequently the overall cell performance.…”
Section: © 2014 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…The good performances of DSCs require improving the charge collection efficiency over the entire semiconducting electrode (generally, titanium dioxide (TiO 2 )) to the contact [13,14]; in particular, the electronic property and the surface area of the photoanode determine the current output of the device [13,15]. Accordingly, good light harvesting ability, charge transport and low recombination are key challenges for hybrid solar cells [16,17]. The charge collection capability of the photoanode is quantified with the diffusion length of the injected charges; recent papers present an LBIC-based technique [18][19][20] to directly extract the absolute value of L; unfortunately, despite the simplicity of the analysis, these techniques require a substrate contact patterning that limits the application to customized devices.…”
Section: Introductionmentioning
confidence: 99%